"Ntombazana, ugayela bani?" : ubunzululwazi beentsimbi - Silo, Tolakele Talitha (Rhodes University, Faculty of Humanities, School of Languages and Literatures, 2020)
" NTOMBAZANA, UGAYELA BANI?" : UBUNZULULWAZI BEENTSIMBI is a study on the culture of abaThembu, one of the amaXhosa subgroups. Focusing on beadwork as one of this group's cultural aspects, this research is an initiative to ensure documentation of such indigenous knowledge as an influence on the lifestyle of abaThembu. It also strives to uplift the use of oral literature to present it a fair chance at being a driving force for change as it has previously been ousted with the acceptability of written literature. Of great surprise is to see that despite western civilization, which affected the people's culture, beadwork remains a pillar of the abaThembu-amaXhosa culture. This craft has evolved and thus, shows no signs of regression. This thesis is an indigenous knowledge focused research.
Keywords: Beadwork, Xhosa; Xhosa (African people) -- Social life and customs; Beadwork, Tembu; Tembu (African people) -- Social life and customs